Política indigenista no Amazonas: as primeiras experiências republicanas (1889-1910) - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Analyzing the indian policy at the early years of the Republic in Amazon is the objective of this research. The set of laws, actions and debates elaborated by the politicians of the time underwent an analysis with the purpose of clarifying their insertion in this new political context and also, highlighting the local specificities. The historical context is the installation of the Republic, marked by the positivist influence in the formation of the new State, at a time when the idea of protecting the natives gains strength in parallel with the catechesis and civilization of the indians. The first step was to investigate the debates of the state deputies, using as a privileged source the annals of the State Legislative Assembly, document destined to record the minutes of the parliamentary sessions, documentary set rich in information. At the same time, it was sought, through the trajectory of some deputies, to understand the place in which they spoke, seeking to reveal their interests. A next step was to examine the Decree number 248 of 1898, document responsible for regulating the catechesis and civilization of the indians in the republican Amazon. Thus, it was sought to trace the way the State of Amazonas worked with indigenous populations. Finally, the effort was to illuminate the repercussion of the indigenist politics beyond the official documents, intending to have access to the other facet on the same subject.
Indigenous policy in the Amazon: the first republican experiences (1889-1910)
Keywords: Indígenas - Relações com o governo; Indígenas - Política e governo; História; Política indigenista; Amazonas; República